Dekonstruksi Pemahaman Surah Al-Qashash Ayat 56 Terhadap Justifikasi Kekafiran Abu Thalib - Agus Anwar Sipahutar; Nur Imam Mahdi; Ahmad Rafiq; Marhumah Marhumah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Deconstruction of Understanding of Surah Al-Qashash Verse 56 Against the Justification of Abu Talib's disbeliefThis paper discusses the deconstruction of the interpretation of the justification of the mufassirin scholars regarding the disbelief of Abu Thalib as the uncle of the Prophet Muhammad in understanding surah al-Qashas verse 56. The author approaches by understanding the tafsir al-ma'tsur. This method is by understanding the verse before surah Al-Qashas verse 56 and after the verse, when the verse already has the same understanding relationship, then looks for verses that have the same topic, then looks for hadiths that have a relevant relationship to the topic being discussed. , so that we arrive at the analysis and the conclusion that the word "ahbabka" in the verse is not referred to as Abu Thalib, but to the uncle of the Prophet. another. So it can be concluded that Abu Thalib lived in a state of faith and died in a state of faith